Surgical technique for mitral valve repair in dogs using a novel method to anchor artificial chordae tendineae with emphasis on key intraoperative decision points - Isayama, Noriko; Mizuno, Takeshi; Suzuki, Sayaka; Sasaki, Kenta; Maeda, Erika; Uchimura, Yusuke (Frontiers in Veterinary Science, 2024)
ObjectivesSurgical options for mitral valve repair in dogs are unstandardized and influenced by various factors. This study describes a four-point surgical technique (MI-4) to reduce mitral regurgitation and provides data from a study of dogs with 12 months of follow up.MethodsTwenty-five dogs with stages C or D mitral insufficiency were treated by one of two surgeons using the MI-4 procedure at Ueno no Mori Animal Hospital between October 2021 and May 2023. The surgical technique comprised: (I) determination of the valve annulus dimensions by measuring between the trigones, (II) triad-anchored chordae tendinea reconstruction, (III) determination of the appropriate position and number of chordae tendineae on the leaflets, and (IV) appropriate height determination. The regurgitation percentage was measured using B-mode color Doppler flow in the atrium in the four-chamber left long-axis view.ResultsThere were no intraoperative complications, and 23, 23, and 18 dogs were successfully re-evaluated at 1, 6, and 12 months, respectively (5 dogs have not yet reached the 12-month follow-up point). The regurgitation percentage decreased from 73.0% (interquartile range, 58.1–81.5%) preoperatively to 2.1% (0.0–8.8%), 4.6% (0.1–10.8), and 1.3% (0.0–7.1) at 1, 6, and 12 months postoperatively, respectively. All surviving dogs improved clinically.ConclusionThe MI-4 surgical technique was performed in dogs with mitral valve insufficiency with no significant complications. The surgery reduced the regurgitation percentage postoperatively, with benefits seen at least 12 months after surgery.